2007
DOI: 10.1111/j.1365-2044.2007.04986.x
|View full text |Cite
|
Sign up to set email alerts
|

Bispectral index values during elective rigid bronchoscopy: a prospective observational pilot study

Abstract: SummaryRigid bronchoscopy is associated with a high incidence of haemodynamic disturbance and awareness under anaesthesia. Anaesthetic agents are given both to attenuate the sympathetic response to bronchoscopy and to prevent awareness. Use of the Bispectral index to guide anaesthesia has shown to reduce awareness and improve recovery times from general anaesthesia. We undertook a prospective observational study of BIS values in 50 patients during routine anaesthesia for rigid bronchoscopy. BIS values were fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…In seven units (3.3%) anaesthesia is provided using intermittent boluses of propofol, without a background infusion. This may be of concern given that one study reported awareness during rigid bronchoscopies [3] and all the patients who reported awareness were anaesthetized using intermittent boluses of propofol. Nine units (4.2%) reported using a BIS during PDT.…”
Section: Resultsmentioning
confidence: 99%
“…In seven units (3.3%) anaesthesia is provided using intermittent boluses of propofol, without a background infusion. This may be of concern given that one study reported awareness during rigid bronchoscopies [3] and all the patients who reported awareness were anaesthetized using intermittent boluses of propofol. Nine units (4.2%) reported using a BIS during PDT.…”
Section: Resultsmentioning
confidence: 99%
“…Intermittent propofol injections instead of continuous infusion during rigid bronchoscopy may be preferred as a practical technique in some centers (17,28), as in our institution. In this study, to decrease the recovery time and risk of awareness, propofol or ketamine infusions instead of bolus doses and bispectral index monitoring may be more appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, to decrease the recovery time and risk of awareness, propofol or ketamine infusions instead of bolus doses and bispectral index monitoring may be more appropriate. However, Bould et al (28) found no difference in the bispectral index (BIS) values of patients anesthetized for elective RB with intermittent boluses or target controlled infusions of propofol. In addition, bispectral index monitoring was found to be unreliable in the case of ketamine use (29).…”
Section: Discussionmentioning
confidence: 99%
“…12 Then again, in an observational study of patients during routine anesthesia for rigid bronchoscopy, Bould et al 2 reported that Manual TCI = manual target-control infusion of propofol and remifentanil guided by the bispectral index. Dual-loop = Automated control of propofol and remifentanil guided by the bispectral index BIS = bispectral index; BIS 40-60 = percentage of time during which the BIS value was 40-60 during the maintenance; BIS \40 = percentage of time during which the BIS value was less than a value of 40; BIS [60 = percentage of time during which the BIS value was greater than a value of 60; SR = burst suppression ratio incidence (i.e., patients who presented a suppression ratio [ 10% during more than one minute) PE = performance error; MDPE = median of performance error or bias; MDAPE = median absolute performance error or inaccuracy; Wobble = intra-individual variability in performance error; GS = global score Automatic administration of propofol-remifentanil 885 usual, as they knew that patients would be interviewed postoperatively to determine explicit recall.…”
Section: Discussionmentioning
confidence: 99%
“…2 Recently, we described a controller that appears to be effective for anesthetic induction and maintenance during common surgical procedures. 3 Rigid bronchoscopy is a particularly challenging procedure.…”
Section: Résumémentioning
confidence: 99%